Wpływ programu „Umiem pływać” na rozwój pływania w województwie Kujawsko-Pomorskim = The influence of the „Umiem pływać” programme on development of swimming in Kujawsko-Pomorskie - Kostyra, Agnieszka (Journal of Education, Health and Sport, 2015)
Kostyra Agnieszka. Wpływ programu „Umiem pływać” na rozwój pływania w województwie Kujawsko-Pomorskim = The influence of the „Umiem pływać” programme on development of swimming in Kujawsko-Pomorskie. Journal of Education, Health and Sport. 2015;5(7):51-62. ISSN 2391-8306. DOI 10.5281/zenodo.19171 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A51-62 https://pbn.nauka.gov.pl/works/576505 http://dx.doi.org/10.5281/zenodo.19171 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 24.06.2015. Wpływ programu „Umiem pływać” na rozwój pływania w województwie Kujawsko-Pomorskim The influence of the „Umiem pływać” programme on development of swimming in Kujawsko-Pomorskie Agnieszka Kostyra Abstract Swimming is a common discipline in Poland, but for many reasons it is not appreciated and it is not highly approved. This is generaly an individual sport in opposit to the group of disciplines such as football or volleyball. With the capabilities, technology and commitment to coaches and swimming instructors have the opportunity to demonstrate their knowledge about learning and improving swimming and creativity in organizing various sports activities. We should remember that coaches are only a part of the whole responsibility of the skills acquired by children in the developing process. A large part of these are their parents and teachers. Thanks to the development and popularization of sport many new swimming programs, such as the „Umiem pływać” are created. This initiative aims in promotion of physical activity of children and young people and acquireing their basic swimming skills. The organization of sports activities helps preventing social pathologies and equalizes opportunities in access to sport infrastructure. Keywords: swimming, physical activity, children, programme, coach. Słowa kluczowe: pływanie, aktywność fizyczna, dzieci, projekt, trener.